Adaptive Physical Education and Sport: Academic Foundations and Contemporary Development Within Inclusive Pedagogy - Kazakbaev, Aydos (Indonesian Journal Publisher, 2025)
This study examines the conceptual foundations, pedagogical approaches, and developmental trends in Adaptive Physical Education and Sport (APES) as a multidimensional system supporting individuals with physical, sensory, and intellectual disabilities. Using a mixed theoretical–analytical methodology, the research synthesizes international frameworks, neurophysiological evidence, pedagogical models, and applied practices to explore how adaptive sport contributes to functional rehabilitation, psychomotor development, and social inclusion. Findings demonstrate that APES is not merely a compensatory form of physical activity but a scientifically grounded system promoting neuroplasticity, emotional resilience, motor independence, and quality of life. Modern adaptive sport, supported by technological innovations such as assistive devices, motion analysis tools, and digital feedback systems, creates new opportunities for personalized instruction. The study concludes that APES represents a strategic component of inclusive education and public health, requiring advanced instructor training, evidence-based methodologies, and interdisciplinary collaboration. Recommendations are provided for enhancing adaptive sport programs particularly in emerging educational environments.